The ‘person of moral growth’: a model of moral development based on personalist virtue ethics - Manuel Joaquín Fernández González; Kleio Akrivou (Cogent Education, 2024)
Moral development is crucial for a meaningful life. Many well-founded approaches and models are present in the moral development literature, which is a very diverse and populated field. The model of a ‘person of moral growth’ presented in this paper is a contribution to moral growth research based on personalist virtue ethics. Personalist virtue ethics puts the person at the centre of the moral reflection, addressing the holistic interplay of the person’s dimensions in the process of moral growth. The model is an operationalization of the person’s dimensions for educational and research purposes in the field of moral development. In this paper, the four components of the model are presented: emotional-cognitive, decisional (free commitment to moral growth), practical (moral growth through personal action), and self-understanding (the moral growth identity), and the process of the elaboration of the model is explained. For enhancing the construct validity of the model, its components and pedagogical implications are discussed in the light of recent moral education literature. This model is a contribution to a more cogent moral education and is helping to design and deliver moral educational experiences which address personal moral development in a clear, convincing, and well-structured way.